Geographic cline analysis as a tool for studying genome‐wide variation: a case study of pollinator‐mediated divergence in a monkeyflower. Issue 1 (10th June 2016) - Stankowski, Sean; Sobel, James M.; Streisfeld, Matthew A.
Abstract: A major goal of speciation research is to reveal the genomic signatures that accompany the speciation process. Genome scans are routinely used to explore genome‐wide variation and identify highly differentiated loci that may contribute to ecological divergence, but they do not incorporate spatial, phenotypic or environmental data that might enhance outlier detection. Geographic cline analysis provides a potential framework for integrating diverse forms of data in a spatially explicit framework, but has not been used to study genome‐wide patterns of divergence. Aided by a first‐draft genome assembly, we combined an F CT scan and geographic cline analysis to characterize patterns of genome‐wide divergence between divergent pollination ecotypes of Mimulus aurantiacus . F CT analysis of 58 872 SNPs generated via RAD‐seq revealed little ecotypic differentiation (mean F CT  = 0.041), although a small number of loci were moderately‐to‐highly diverged. Consistent with our previous results from the gene MaMyb2, which contributes to differences in flower colour, 130 loci have cline shapes that recapitulate the spatial pattern of trait divergence, suggesting that they may reside in or near the genomic regions that contribute to pollinator isolation. In the narrow hybrid zone between the ecotypes, extensive admixture among individuals and low linkage disequilibrium between markers indicate that most outlier loci are scattered throughout the genome, rather than being restricted to one or a few divergent regions. In addition to revealing the genomic consequences of ecological divergence in this system, we discuss how geographic cline analysis is a powerful but under‐utilized framework for studying genome‐wide patterns of divergence.